Analysis of Affective Assessment in Measuring Elementary School Students' Critical Reasoning Ability in View of Gender - Dianasari Dianasari; Bunyamin Maftuh; Ernawulan Syaodih; Sapriya Sapriya (UM Purwokerto Press, 2024)
Affective assessment in looking at elementary school students' critical reasoning abilities is considered to need to be analyzed as a complex process of changing students' attitudes in implementing the Pancasila student profile. Analysis involves receiving and mastering data, data analysis, and data evaluation, which must be taught to students because these skills are very necessary in life. The aim of the research was to analyze the affective assessment of elementary school students' critical reasoning abilities in terms of gender. The research method used is quantitative research. The research subjects were 32 students in Class 5 of Keraton 1 State Elementary School for the 2024/2025 academic year, divided into 12 male students and 20 female students. Data analysis used the independent t test. The results of the research show that there is no significant difference in the form of affective assessment of critical reasoning ability, in terms of the gender of class V students. The results of the independent t test obtained a significance value of 0.204 > 0.05, meaning that the average critical reasoning ability of women (3.205) is higher. higher than men (3.085) with a difference of 1.120 which is considered not significant. The results of critical reasoning indicators (seeking information, assessing information, making conclusions, and making decisions) show that there are no significant differences based on student gender. The implication of the research is that teachers are able to improve critical reasoning skills, researchers can then analyze other factors or develop other research objects.